RANCANG BANGUN ALAT PENGUPAS KULIT BUAH ASAM (TAMARINDUS INDICA) MENGGUNAKAN MEKANISME CENTRIFUGAL IMPACT - Maubila, Julian Marthin; Maliwemu, Erich U.K; Tobe, Adi Yeremia (TURBO [Tulisan Riset Berbasis Online], 2023)
Tamarind farmers generally use the traditional method, namely by using their fingers to peel the skin of the tamarind fruit, in addition to using their fingers the other traditional way and also using their hands by putting the acid into a sack and then hitting it with a hard object, this traditional method requires a lot of time to peel the skin. acid and separates the tamarind peel from the sour fruit flesh. Acid peeling tools are needed as a means to help farmers need to peel tamarind and make it easier to peel and also save time and energy in peeling tamarind. The design of tamarind peeler aims to produce a design and manufacture of tamarind peeler for the needs of tamarind farmers in East Nusa Tenggara. The results of the design of an acid peeler which is made using a centrifugal impact mechanism so as to make the tamarind peel breakable and can be separated from the sour fruit flesh with production result 180 kg/hour, at least 4 days of driying.